2006
DOI: 10.1124/jpet.106.101618
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Analogs Increase Plasma Serotonin: Implications for Cardiac and Pulmonary Disease

Abstract: Elevations in plasma serotonin (5-HT) have been implicated in the pathogenesis of cardiac and pulmonary disease. Normally, plasma 5-HT concentrations are kept low by transporter-mediated uptake of 5-HT into platelets and by metabolism to 5-hydroxyindoleacetic acid (5-HIAA). Many abused drugs (e.g., substituted amphetamines) and prescribed medications (e.g., fluoxetine) target 5-HT transporters and could thereby influence circulating 5-HT. We evaluated the effects of amphetamines analogs [(Ϯ)-fenfluramine, (Ϯ)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…The finding that citalopram in vitro was able to partially reverse the effects of MA on MAO-A activity further supports the concept that MA enters epithelial cells via SERT, and this is blocked by the reuptake inhibitor, citalopram. As demonstrated by Zolkowska and colleagues (14), SSRIs may themselves cause transient increases in circulating 5-HT. However, these transient increases resolve within 60 minutes after administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that citalopram in vitro was able to partially reverse the effects of MA on MAO-A activity further supports the concept that MA enters epithelial cells via SERT, and this is blocked by the reuptake inhibitor, citalopram. As demonstrated by Zolkowska and colleagues (14), SSRIs may themselves cause transient increases in circulating 5-HT. However, these transient increases resolve within 60 minutes after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Zolkowska and colleagues (14) reported that intravenous administration of MA in rats resulted in increased plasma 5-HT concentrations. Given 5-HT is an effective bronchoconstrictor and other amphetamine analogs have been shown to inhibit 5-HT metabolism to 5-HIAA (13), we assessed whether 5-HT metabolism was altered in lungs from MA-exposed mice.…”
Section: -Ht Metabolism In the Lung After Exposure To Ma Vapormentioning
confidence: 99%
See 1 more Smart Citation
“…Given the uncertainties regarding the validity of the 5-HT hypothesis, we developed a novel microdialysis method to measure plasma levels of 5-HT in whole-blood samples from conscious catheterized rats that involves careful blood handling to minimize the chance of platelet lysis (Zolkowska et al, 2006). Using this method, we reported that baseline dialysate levels of 5-HT in blood are ϳ0.22 nM (or ϳ0.88 nM when corrected for probe recovery), and fenfluramine and other potent SERT substrates evoke transient dose-dependent increases in plasma 5-HT ranging from 4 to 20 nM.…”
mentioning
confidence: 99%
“…Plasma 5-HT is increased in rats treated with fenfluramine, or its D-isomer dexfenfluramine [10][11][12]. This may occur because dexfenfluramine blocks uptake of 5-HT by the 5-HTT but if that were the only mechanism of the associated PAH in patients, then the serotonin reuptake inhibitors (SSRIs), such as fluoxetine, which are widely used, would cause PAH.…”
Section: Elevation Of Plasma 5-ht Levelsmentioning
confidence: 99%